Review of load-bearing capacity of dented pipes under typical loads. (February 2021) - Zhang, Ping; Lan, Huiqing; Dou, Xiran; Wang, Junqiang; Zha, Sixi
Highlights: Provides a comprehensive understanding in the load-bearing capacity of dented pipes. Some dents with scratches do not affect the bursting pressure of the pipe. The depth-based assessment method is inapplicable to the pipe with folded dent. The critical bending strain of plain dent calculated has a limited application. No experiments can be used to study residual strength of pipes under combined loads. Abstract: Dent is a common geometric deformation defect on oil and gas pipelines. Compared with plain dent, composite dent has a greater impact on the pipe's load-bearing capacity. There are great differences in the evaluation methods about dent under different loads, and it is significant in practical engineering to study the load-bearing capacity of dented pipes under specific working conditions. This paper summarizes the research status of load-bearing capacity of dented pipes under internal pressure, bending moment, axial force and combined loads in recent years from the aspects of experiment and simulation, analyses the progress of relevant evaluation criteria, and points out the shortcomings and future research directions. At present, corresponding evaluation criteria have been proposed for crack dent under internal pressure, plain dent under bending moment and folded dent under axial compression. The formula for calculating the critical compressive strain of plain dent under bending moment is relatively mature. However, the study on the dent at welds is insufficiency, and the depth-based evaluation method is not suitable for folded dent. Furthermore, the residual strength of dented pipes under combined loads has not attracted much attention.